Anchoring a secreted plasmodium antigen on the surface of recombinant vaccinia virus-infected cells increases its immunogenicity. - Langford, C J (1986)
We show that the subcellular location of foreign antigens expressed in recombinant vaccinia viruses influences their effectiveness as immunogens. Live recombinant viruses induced very poor antibody responses to a secreted repetitive plasmodial antigen (the S-antigen) in rabbits and mice. The poor response accords with epidemiological data suggesting that S-antigens are poorly immunogenic. Appending the transmembrane domain of a membrane immunoglobulin (immunoglobulin G1) to its carboxy terminus produced a hybrid S-antigen that was no longer secreted but was located on the surface of virus-infected cells. This recombinant virus elicited high antibody titers to the S-antigen. This approach will facilitate the use of live virus delivery systems to immunize against a wide range of foreign nonsurface antigens.